STRATEGI INTENSIFIKASI DAN EKSTENSIFIKASI DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN PAMEKASAN - Salehoddin, Salehoddin (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2019)
Concrete steps that need to be taken by the Government of Pamekasan Regencyand its staff to further optimize the acquisition of local taxes and local user fees, namelyby conducting an Intensification and Extensification Strategy. The purpose of this research is to conduct analysis of Strengths, Weakness,Opportunities, Threats (SWOT) on issues related to efforts to increase the RegionalOriginal Revenue (PAD) of Pamekasan Regency, and to find out the Strategic Plan forthe Intensification and Extensification of the Pamekasan Regency Government inincreasing the District Revenue Pamekasan. While this study uses a descriptivequalitative approach, which is research that requires a deep and comprehensiveunderstanding related to the object under study to answer the problem by getting data tothen be analyzed and concluded. The Intensification Strategy is carried out in the following ways: Managing theTax and Retribution Administration Management System, Optimizing the collection ofTaxes and Levies through the application of the discipline of tax and retributionpayments to avoid the "Gap of tax and retribution receivable", Supervising andcontrolling systematic and sustainable by forming a Task Force Team (Satgas), Providingincentives to the Regional Apparatus Organizations that in the collection of taxes andretribution meet the targets set. The Extensification Strategy, carried out in the following ways, is as follows: Exploring and creating new tax and retribution objects, Conducting a review of theimposition of tax and retribution rates which so far have not been adjusted for tariffs andconducting comparative studies on regions that apply the "Management System Taxesand levies "good and achievers.Keyword : Intensification and Extensification Strategy